Altered Circulating MicroRNA Profiles After Endurance Training: A Cohort Study of Ultramarathon Runners - Eyileten, Ceren; Wicik, Zofia; Fitas, Alex; Marszalek, Mikolaj; Simon, Jenny E.; De Rosa, Salvatore; Wiecha, Szczepan; Palatini, Jeffrey; Postula, Marek; Malek, Lukasz A. (Frontiers in Physiology, 2022)
Background: Despite the positive effects of endurance training on the cardiovascular (CV) system, excessive exercise induces not only physiological adaptations but also adverse changes in CV system, including the heart. We aimed to evaluate the selected miRNAs expression based on bioinformatic analysis and their changes before and after an ultramarathon run. Materials and Methods: Cardiac tissue-specific targets were identified with the Tissue 2.0 database. Gene-gene interaction data were retrieved from the STRING app for Cytoscape. Twenty three endurance athletes were recruited to the study. Athletes ran to completion (100 km) or exhaustion (52 - 91 km, median 74 km). All participants completed pre- and post-run testing. miRNAs expressions were measured both before and after the race. Results: Enrichment analysis of the signaling pathways associated with the genes targeted by miRNAs selected for qRT-PCR validation (miR-1-3p, miR-126, miR-223, miR-125a-5p, miR-106a-5p, and miR-15a/b). All selected miRNAs showed overlap in regulation in pathways associated with cancer, IL-2 signaling, TGF-β signaling as well as BDNF signaling pathway. Analysis of metabolites revealed significant regulation of magnesium and guanosine triphosphate across analysed miRNA targets. MiR-1-3p, miR-125a-5p, miR-126, miR-223 expressions were measured in 23 experienced endurance athletes, before and after an ultramarathon wherein athletes ran to completion (100 km) or exhaustion (52 - 91 km, median 74 km). The expressions of miR-125a-5p, miR-126 and miR-223 were significantly increased after the race (p=0.007, p=0.001, p=0.014, respectively). MiR-1-3p expression post-run showed a negative correlation with the post-run levels of high-sensitivity C-reactive protein (hsCRP) (r= -0.632, p=0.003). Higher miR-1-3p expression was found in runners, who finished the race under 10 hours compared to runners finished over 10 hours (p=0.001). Post-run miR-125a-5p expression showed a negative correlation with the peak lactate during the run (r= -0.742, p=0.004). Conclusion: Extreme physical activity, as exemplified by an ultramarathon, is associated with changes in circulating miRNAs’ expression related to inflammation, fibrosis, and cardiac muscle function. In particular, the negative correlations between miR-125a-5p and lactate concentrations, and miR-1-3p and hsCRP, support their role in specific exercise-induced adaptation. Further studies are essential to validate the long-term effect of these observations.